2021
DOI: 10.3201/eid2702.202047
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus–Associated Birth Defects, Costa Rica, 2016–2018

Abstract: In support of improving patient care, this activity has been planned and implemented by Medscape, LLC and Emerging Infectious Diseases. Medscape, LLC is jointly accredited by the Accreditation Council for Continuing Medical Education (ACCME), the Accreditation Council for Pharmacy Education (ACPE), and the American Nurses Credentialing Center (ANCC), to provide continuing education for the healthcare team. Medscape, LLC designates this Journal-based CME activity for a maximum of 1.00 AMA PRA Category 1 Credit(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Both symptomatic and asymptomatic ZIKV infections in pregnancy have been reported to cause ZIKV-related birth anomalies. The national birth defects surveillance system in Costa Rica reported that 64% of all infants with Zika-associated anomalies were born to women who reported Zika-like symptoms, thus, 36% of these children were born to asymptomatic women [40].…”
Section: Microcephaly and Congenital Zika Syndromementioning
confidence: 99%
“…Both symptomatic and asymptomatic ZIKV infections in pregnancy have been reported to cause ZIKV-related birth anomalies. The national birth defects surveillance system in Costa Rica reported that 64% of all infants with Zika-associated anomalies were born to women who reported Zika-like symptoms, thus, 36% of these children were born to asymptomatic women [40].…”
Section: Microcephaly and Congenital Zika Syndromementioning
confidence: 99%
“…org/ hq/ dmdocuments) up until January 2018 indicate that, in the registries in this study, the highest prevalences of CZS occurred in Brazil and Colombia and slightly lower ones in Costa Rica, which would be confirmed by the large increases in prevalence observed in Brazil, Bogota and Cali and the increases in Costa Rica. 7 However, Argentina reported five cases to PAHO/ WHO, which were identified in the data and they do not account for the increases in microcephaly observed in Argentina from 2015 to 2017, indicating these increases are likely due to be to improved diagnosis or more reporting of microcephaly. It is possible that other countries also observed an increase in prevalence of microcephaly which was partly due to Zika, and partly due to increased reporting.…”
Section: Open Accessmentioning
confidence: 82%
“…Open access of ReLAMC. The prevalence of microcephaly was chosen, due to its association with the Zika virus epidemic and the associated interest in changes in its prevalence over the time of the epidemic observed in other studies [4][5][6][7][8][9][10][11][12] and the lack of accurate information due to underreporting in the PAHO/WHO Zika virus surveillance system. 13 In addition to the Zika virus, the STORCH infections ((s) yphilis, (t)oxoplasmosis, (o)ther agents, (r)ubella, (c) ytomegalovirus and (h)erpes simplex infection) are associated with microcephaly in the fetuses and therefore information about STORCH infections is also important to report.…”
Section: What This Study Adds?mentioning
confidence: 99%
“…It is conceivable that pregnant women infected with JEV may pass the virus to their fetus, based on the recent findings that during gestation, ZIKV can cross the placenta, infect the unborn offspring, and thus cause miscarriage or a variety of birth defects, collectively designated as congenital Zika syndrome, such as microcephaly [ 194 ]. However, little is known about the possible adverse effects of JEV infection during pregnancy.…”
Section: Clinical Features In Humansmentioning
confidence: 99%